Cold indoor temperatures and their association with health and well-being: a systematic literature review - Janssen, H.; Ford, K.; Gascoyne, B.; Hill, R.; Roberts, M.; Bellis, M.A.; Azam, S. (Public health (London), 2023)
The study aimed to identify, appraise and update evidence on the association between cold temperatures (i.e. <18°C) within homes (i.e. dwellings) and health and well-being outcomes. This study was a systematic review. Seven databases (MEDLINE, Embase, Cochrane Database of Systematic Reviews, CINAHL, APA PsycInfo, Applied Social Sciences Index and Abstracts, Coronavirus Research Database) were searched for studies published between 2014 and 2022, which explored the association between cold indoor temperatures and health and well-being outcomes. Studies were limited to those conducted in temperate and colder climates due to the increased risk of morbidity and mortality during winter in those climatic zones. Studies were independently quality assessed using the Quality Assessment Tool for Observational Cohort and Cross-Sectional Studies. Of 1209 studies, 20 were included for review. Study outcomes included cardiovascular (blood pressure, electrocardiogram abnormalities, blood platelet count), respiratory (chronic obstructive pulmonary disease symptoms, respiratory viral infection), sleep, physical performance and general health. Seventeen studies found exposure to cold indoor temperatures was associated with negative effects on health outcomes studied. Older individuals and those with chronic health problems were found to be more vulnerable to negative health outcomes. Evidence suggests that indoor temperatures <18°C are associated with negative health effects. However, the evidence is insufficient to allow clear conclusions regarding outcomes from specific temperature thresholds for different population groups. Significant gaps in the current evidence base are identified, including research on the impacts of cold indoor temperatures on mental health and well-being, studies involving young children, and the long-term health effects of cold indoor temperatures.